Supercritical carbon dioxide fractionation of palm kernel oil and formulation of cocoa butter replacers fat. - Sarker, Md. Zaidul Islam (2003)
The extraction of dehulled ground palm kernel using supercritical carbon dioxide (SC-C02) as a solvent at temperatures of 40 and 80°C and pressures of 20.7,27.6, 34.5, 41.4 and 48.3 MPa was studied. Continuous extraction was fractionated into four fractions and each fraction was collected for every 10 minutes. Thus the total extraction process was performed for 40 minutes extraction time.